The efficacy of neuro-optometric visual rehabilitation therapy in patients with visual snow syndrome - Tsang, Terry; Shidlofsky, Charles; Mora, Vanessa (Frontiers in Neurology, 2022)
Objective This study intends to evaluate the feasibility of Neuro-Optometric Rehabilitation Therapy (NORT) to treat Visual Snow Syndrome (VSS). This pilot study utilized the National Eye Institute Visual Function Questionnaire (NEI-VFQ-25) to assess quality of life (QOL) before and after treatment. Methods Twenty-one participants were recruited as successive intake patients diagnosed with VSS at the clinics of Dr. Terry Tsang Optometry, Inc and Neuro-Vision Associates of North Texas. Participants completed the NEI Visual Function Questionnaire 25-2000 edition and performed NORT, conducted by a neuro-optometrist or a qualified vision therapist. The NEI-VFQ-25 was administered before, at 6 weeks, and at 12 weeks of NORT to evaluate the effects of treatment on patient QOL. Results The participants demonstrated an improvement in QOL composite and subscale scores after 6 and 12 weeks of NORT treatment. The NEI-VFQ-25 composite scores from the pre-test (M = 68, SD = 18) and at 6 weeks of treatment (M = 75, SD = 17) indicate an improvement in QOL [t (20) = 4.0, p = 0.0007]. The NEI-VFQ-25 composite scores from pretest to 12 weeks of treatment showed further improvements. This trend of improvement on NEI-VFQ-25 composite scores continued into the 12th week (M = 77, SD = 17) of treatment [t (20) = 4.5, p = 0.0002]. The subscales of general vision, distance activities, near activities, social functioning, mental health, role difficulties and dependency also showed improvement. Conclusion Our results suggest that patients with VSS experience improvement in QOL in as little as 6 weeks, with further improvement by 12 weeks of NORT. This suggests NORT is an effective treatment option for managing the condition and improving QOL in patients with VSS, although a reduction in specific symptoms has yet to be demonstrated. This study provides justification that NORT warrants further investigation on VSS symptom reduction.